Implementation of the Child Care and Education Module in the Family Development Session Program PKH - Meli Sutri Yani; Wisroni Wisroni (Universitas Negeri Padang, 2021)
This research was motivated by the successful implementation of the child care and education module in the FDS program in Lolong Belanti Village, Padang City. This study aims to see the description of the implementation of the child care and education module in the FDS program based on aspects of efficiency, effectiveness and responsiveness. This type of research is descriptive quantitative research. The population in this study amounted to 86 KPM. The sampling technique was cluster random sampling, with a total of 43 people. Data collection techniques using a questionnaire. The data analysis technique uses the percentage formula. The results showed that (1) the efficiency of the implementation of the Parenting and Child Education module was obtained at an interval of 93% in the very appropriate category, (2) The effectiveness of the implementation of the Parenting and Child Education module obtained an interval of 93% in the very appropriate category, and (3) the responsiveness of implementation Parenting and Child Education module, obtained 98% interval is in the very category.